Dominican baseball : new pride, old prejudice - Klein, Alan, 1946- (Temple University Press, 2014)
Alan Klein examines the history of Major League Baseball's presence and influence in the Dominican Republic, the development of the booming industry and academies, and the dependence on Dominican player developers, known as buscones. He also addresses issues of identity fraud and the use of performance-enhancing drugs as hopefuls seek to play professionally. Dominican Baseball charts the trajectory of the economic flows of this transnational exchange, and the pride Dominicans feel in their growing influence in the sport. Klein also uncovers the prejudice that prompts MLB to diminish Dominican claims on legitimacy.